Identifying enablers for a circular healthcare supply chain: an integrated fuzzy DEMATEL-MMDE approach with hesitant information - Agrawal, Deepak; Gupta, Sumit; Dusad, Chandni; Meena, M. L.; Dangayach, Govind Sharan; Jagtap, Sandeep (Elsevier, 2025)
Over the past decade, the healthcare industries have been facing the issue of resource scarcity due to socio-political wars, the COVID-19 pandemic, the luxury lifestyles of people, and the prevalence of single-use medical devices. The circular economy (CE) can be vital in accommodating the evolving patient and provider demands. The CE defies the conventional take-make-dispose process and advocates for optimized resource use throughout its entire lifecycle. Finding the critical enabler for a circular supply chain in the Indian healthcare sector is urgently needed because the CE is still nascent in developing nations like India. This paper identifies the enablers of a circular healthcare supply chain (CHSC) through a comprehensive analysis of cause and effect, interrelationships, and priorities using integrated alpha-level sets based on the fuzzy DEMATEL-MMDE approach with hesitant information. Experts' opinions were gathered using a triangular fuzzy linguistic scale, incorporating hesitant information to minimize data vagueness. The results of this study offer valuable insights into various enablers, emphasizing their criticality and interdependence, thereby benefiting healthcare organizations aiming to implement circular supply chains. Additionally, the findings will assist policymakers in creating policies to accelerate the adoption of CE practices in the healthcare industry.
Keywords: 40 Engineering; 4011 Environmental Engineering; Generic health relevance; 12 Responsible Consumption and Production; Healthcare supply chain; Enablers; Circular economy; DEMATEL; MMDE; Fuzzy linguistic term sets; Alpha level sets